1993
DOI: 10.1136/bmj.306.6872.240
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria: associations with height and sex in non-diabetic subjects.

Abstract: Objectives-To study the association(s) between microalbuminuria and cardiovascular risk factors in non-diabetic subjects.Design-Patients aged 40-75 years were randomly selected from a general practice list and invited to participate.Setting-Health centre in inner city London. Subjects-Of those invited, 1046 out of 1671 (62/6%) attended. Subjects were excluded for the following reasons: not being white (44); urinary albumin excretion rate >200 pLg/min (3); having a urinary infection (5); taking penicillamine or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
6
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 13 publications
5
56
6
1
Order By: Relevance
“…Based on a similar relationship observed in British men, 27 Yudkin 28 proposed that it might re¯ect early environmental in¯uences that predispose to later cardiovascular disease. Most European New Zealanders are of British descent and 39.8% of participants (41.7% men and 33.9% women) in this study were not born in New Zealand.…”
Section: Discussionmentioning
confidence: 81%
“…Based on a similar relationship observed in British men, 27 Yudkin 28 proposed that it might re¯ect early environmental in¯uences that predispose to later cardiovascular disease. Most European New Zealanders are of British descent and 39.8% of participants (41.7% men and 33.9% women) in this study were not born in New Zealand.…”
Section: Discussionmentioning
confidence: 81%
“…Finland, FINRISK-1987 [37] Finland, East-West Finland [36] Finland, Oulu [40] Sweden, Northern Sweden MONICA Survey [45] Finland, FINRISK-1992 [37] Sweden, Malmö (MPP) [24] Study UK, Cambridge (Ely) [47] Finland, Vantaa [41] Poland, Krakow [44] The Netherlands, Hoorn [43] Italy, Cremona [42] Denmark, Glostrup [35] Finland, FINRISK-2002 [38] Sweden, Uppsala [46] UK, Goodinge [48] UK, Newcastle [49] Finland, Helsinki policemen [39] 1.06 (1.02−1.09) Fig. 1 HR (black circle) and 95% CI (horizontal line) of allcancer death corresponding to a study-specific one SD increase in fasting plasma glucose for each study cohort and for all cohorts pooled together.…”
Section: Resultsmentioning
confidence: 99%
“…Finland, FINRISK-1987 [37] Finland, East-West Finland [36] Italy, Cremona [42] Finland, FINRISK-2002 [38] Sweden, Uppsala [46] Finland, Helsinki policemen [39] Study Poland, Krakow [44] Finland, FINRISK-1992 [37] Sweden, Northern Sweden MONICA Survey [45] Sweden, Malmö (MPP) [24] UK, Newcastle [49] UK, Goodinge [48] Finland, Vantaa [41] The Netherlands, Hoorn [43] Finland, Oulu [40] Denmark, Glostrup [35] UK, Cambridge (Ely) [47] 1.07 (1.03−1.11) …”
Section: Resultsmentioning
confidence: 99%
“…These results agree with our conclusion that there are gender differences in the impact of cardiovascular risk factors on UAE. In a study in non-diabetic subjects, Gould et al (8) showed that UAE was positively associated with age, BP (SBP and DBP), and fasting plasma glucose and negatively associated with height in men, whereas SBP was the only factor associated with UAE in women. These authors (as well as the DESIR authors) used two different models for studying the difference between genders, while we used one model to determine gender differences.…”
Section: Discussionmentioning
confidence: 99%